Proximal tubular cell sodium concentration in early diabetic nephropathy assessed by electron microprobe analysis. - Pollock, C; Field, M; Bostrom, T; Dyne, M; Gyory, A; Cockayne, D (1991)
Electron microprobe X-ray analysis techniques were employed in order to assess the changes that occur in proximal tubular cell sodium concentration during the hyperfiltration phase of early diabetes mellitus induced by streptozotocin in Sprague Dawley rats. Intracellular rubidium accumulation following intravenous infusion of rubidium chloride was used as a marker of basolateral Na/K-ATPase activity. The diabetic animals studied had a significantly higher glomerular filtration rate compared with controls [1.44 +/- 0.07 vs. 1.00 +/- 0.07 ml min-1 (100 g body weight)-1; mean +/- SEM, P less than 0.001]. Intracellular Na concentration was significantly higher in diabetic animals (19.5 +/- 0.6 vs. 17.8 +/- 0.4 mmol/kg wet weight; P less than 0.01). Concurrent measurement of Rb demonstrated significantly higher intracellular accumulation in the proximal tubules of diabetic animals compared with control (7.9 +/- 0.5 vs. 5.5 +/- 0.5 mmol/kg wet weight; P less than 0.001). These results indicate that proximal tubular Na/K-ATPase activity is enhanced in the hyperfiltration phase of diabetes mellitus. Since, however, intracellular Na concentration is increased under these conditions, it may be inferred that apical Na entry into proximal tubular cells is stimulated beyond the rate of basal exit during the initial development of hyperfiltration. The reasons for these alterations in cellular Na transport are unclear but similar changes have been implicated in the pathogenesis of cell growth.